Galileo IOV RTK positioning: standalone and combined with GPS - Odijk, Dennis; Teunissen, Peter; Khodabandeh, A. (Maney Publishing, 2014)
Results are presented of real time kinematic (RTK) positioning based on carrier phase and code (pseudorange) observations of the four Galileo In-Orbit Validation (IOV) satellites, as they were in orbit and transmitting navigation data at the time of writing this article (2013). These Galileo data were collected by multi-GNSS receivers operated by Curtin University and as such this article is one of the first presenting results of short baseline ambiguity resolution and positioning based on Galileo IOV observations. The results demonstrate that integer ambiguity resolution based on the four IOV satellites needs fewer than three minutes when at least observables from three frequencies are used. Combined with data of four GPS satellites even instantaneous (single epoch) ambiguity resolution is demonstrated, using only two frequencies per constellation (i.e. E1+E5a & L1+L2). We also show that at locations with obstructed satellite visibility, such that positioning based on either GPS-only or Galileo-only becomes impossible or only in a very inaccurate way, combined Galileo&GPS positioning is feasible, within 10 min if one frequency of each constellation is used and only 2 min time-to-fix the ambiguities based on observations of two frequencies of each constellation. It is furthermore demonstrated that this results in positions with centimetre level accuracy in the horizontal plane and sub-decimetre accuracy in the vertical direction.